2023
DOI: 10.1177/14614448231215348
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of why gaming communities may make younger and non-normative gamers vulnerable to Internet Gaming Disorder

Enrico Gandolfi,
Richard E Ferdig,
Karlie Krause
et al.

Abstract: Existing literature has primarily evaluated how exposure to video game content impacts social and behavioral functioning. However, the parameters of video game engagement have expanded with multiplayer online gaming, live streaming, and community discussion on social media platforms. This study sought to examine how participation in online gaming communities is associated with problematic gaming behaviors and symptoms of Internet gaming disorder (IGD). A sample of 1176 gamers completed an online survey investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Being part of an online gaming community is important for the development of gaming-related identity (Sirola et al, 2021). However, it was also shown that online communities play an important role in informing GD (Gandolfi et al, 2023), and community engagement can motivate escalation of gaming and in-game purchasing behaviours (Sirola et al, 2021). Furthermore, unlike many other addictive behaviours, gaming is accessible to very young children.…”
Section: Introductionmentioning
confidence: 99%
“…Being part of an online gaming community is important for the development of gaming-related identity (Sirola et al, 2021). However, it was also shown that online communities play an important role in informing GD (Gandolfi et al, 2023), and community engagement can motivate escalation of gaming and in-game purchasing behaviours (Sirola et al, 2021). Furthermore, unlike many other addictive behaviours, gaming is accessible to very young children.…”
Section: Introductionmentioning
confidence: 99%